2004
DOI: 10.1677/erc.1.00778
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor-driven mechanisms associated with resistance to estrogen deprivation in breast cancer: new opportunities for therapy

Abstract: There is an increasing body of evidence demonstrating that elevated growth signaling in breast cancer cells can promote forms of endocrine resistance in either an estrogen receptor-dependent or -independent manner. The current article reviews what is known about such growth factor signaling networks and resistance to estrogen withdrawal and considers the many novel therapeutic opportunities that stem from this knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 107 publications
(76 reference statements)
0
80
0
1
Order By: Relevance
“…Moreover, promotion of ER negativity appears achievable in vitro when hormone-responsive cells are subject to sustained EGFR signalling during very prolonged ER blockade. This is exemplified by our MCF-7 model that, after extended culture with the pure antioestrogen faslodex, gains EGFR signalling but completely lacks ER, a feature irreversible on antioestrogen withdrawal (Nicholson et al 2004c). Further supportive evidence can be drawn from transfection studies where constitutively active components of EGFR/HER2 signalling introduced into ER + MCF-7 cells (notably MEK1…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, promotion of ER negativity appears achievable in vitro when hormone-responsive cells are subject to sustained EGFR signalling during very prolonged ER blockade. This is exemplified by our MCF-7 model that, after extended culture with the pure antioestrogen faslodex, gains EGFR signalling but completely lacks ER, a feature irreversible on antioestrogen withdrawal (Nicholson et al 2004c). Further supportive evidence can be drawn from transfection studies where constitutively active components of EGFR/HER2 signalling introduced into ER + MCF-7 cells (notably MEK1…”
Section: Introductionmentioning
confidence: 74%
“…However, our group has demonstrated that complete dislocation from ER is also possible when growth factor signalling is substantially elevated. Exposure of MCF-7 cells to the ERBB ligand heregulin, which markedly upregulates MAPK and AKT signalling, is associated with lack of response to all endocrine manipulation (Nicholson et al 2004c). Similarly, secondline response to faslodex in our acquired TAMR cells can be abrogated by further hyperactivation of EGFR/ HER2 signalling by several exogenous EGFR ligands (Hutcheson et al 2003, Nicholson et al 2004c).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Suppression of ERa expression through the mechanisms that we have above described might have a role in this phenomenon. In this regard, Nicholson et al (2004) have recently reported that fulvestrantresistant cells lost expression of ERa following prolonged exposure to anti-estrogen. Expression of ERa did not resume in fulvestrant-resistant cells following removal of the drug, and it was associated with the development of an estrogen-independent phenotype.…”
Section: Growth Factor Signaling In Resistance To Endocrine Therapymentioning
confidence: 99%
“…To address this question, studies have been undertaken to investigate longterm estrogen deprivation (LTED), since AIs function to effectively block the synthesis of estrogens. LTED cells have been generated in Dr. R. Santen's, Dr. M. Dowsett's, Dr. R. Nicholson's and Dr. A. Brodie's laboratories [31][32][33][34]. The key findings from these laboratories have been reviewed in a recent report [35].…”
Section: Acquired Resistancementioning
confidence: 99%